2023
DOI: 10.1084/jem.20221751
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps and extracellular histones potentiate IL-17 inflammation in periodontitis

Abstract: Neutrophil infiltration is a hallmark of periodontitis, a prevalent oral inflammatory condition in which Th17-driven mucosal inflammation leads to destruction of tooth-supporting bone. Herein, we document that neutrophil extracellular traps (NETs) are early triggers of pathogenic inflammation in periodontitis. In an established animal model, we demonstrate that neutrophils infiltrate the gingival oral mucosa at early time points after disease induction and expel NETs to trigger mucosal inflammation and bone de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…However, whether MGFs also possess SCC-like potential and participate in the regulation of periodontal homeostasis via taste transduction pathway has yet to be investigated. We first re-analyzed sequence data deposited in the GEO RNA-seq database ( 24 , 25 ). We found that the expression of Tas2r143 was only reported in 2 of the 6 RNA-seq databases, and only one of these databases reported the expression of Gnat3.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether MGFs also possess SCC-like potential and participate in the regulation of periodontal homeostasis via taste transduction pathway has yet to be investigated. We first re-analyzed sequence data deposited in the GEO RNA-seq database ( 24 , 25 ). We found that the expression of Tas2r143 was only reported in 2 of the 6 RNA-seq databases, and only one of these databases reported the expression of Gnat3.…”
Section: Discussionmentioning
confidence: 99%
“…This process leads to the enhanced production of both proinflammatory and regulatory cytokines. The cytokines promote further inflammation, leading to further inflammatory damage (secondary injury) to the periodontal tissues (Figure B). , The gingival epithelium prevents bacterial invasion via the continuous shedding and renewal of cells, and the connective tissue in the subgingival sulcus increases the thickness of the keratinized area in the presence of inflammation . The epithelial barrier is broken down, and a new environment is formed due to continued bacterial attacks and uncontrolled gingival inflammation.…”
Section: The Role Of Hydrogel In the Treatment Of Periodontitismentioning
confidence: 99%
“…Numerous research have indicated that neutrophil extracellular traps (NETs) are composed of chromatin DNA fragments covered with granulated proteins, which are released by neutrophils to ensnare microorganisms. 4 , 5 , 6 , 7 , 8 , 9 , 10 Cancer invasion, evasion, and metastasis have also been associated with the genetic material of NETs (NET‐DNA) in recent research studies. 11 , 12 , 13 , 14 , 15 , 16 Moreover, the importance of CCDC25 expression in NET‐DNA cannot be overstated, as it has been detected in numerous cancer types such as cholangiocarcinoma, gastric cancer, hepatocellular carcinoma, and myeloma.…”
Section: Introductionmentioning
confidence: 99%